2002
DOI: 10.1079/phn2001317
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of energy intake is less common among pregnant women in Indonesia

Abstract: Objectives: To evaluate the ratio of reported energy intake to basal metabolic rate (EI/BMR) among pregnant Indonesian women, as well as identifying risk factors for being an underreporter. Design: Longitudinal study of dietary intake, using six repeated 24-hour diet recalls each trimester. Basal metabolic rate was estimated from body weight and physical activity from occupation. The lower 95% confidence interval for plausible EI/BMR was calculated and the proportion of underreporters estimated. Risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 21 publications
(32 reference statements)
3
45
1
6
Order By: Relevance
“…Individuals with a lower income might have more difficulties in the reporting tasks. Although some studies already observed that underreporters have lower income or education (Winkvist et al, 2002), the discriminant analysis used in our study allowed us to observe the importance of this variable. One may argue that income was highly relevant in this study because it was conducted in a developing country.…”
Section: Discussionmentioning
confidence: 89%
“…Individuals with a lower income might have more difficulties in the reporting tasks. Although some studies already observed that underreporters have lower income or education (Winkvist et al, 2002), the discriminant analysis used in our study allowed us to observe the importance of this variable. One may argue that income was highly relevant in this study because it was conducted in a developing country.…”
Section: Discussionmentioning
confidence: 89%
“…Two previous studies in middle-income countries 29 estimated underreporting of 43% (for FFQ data) in South Africa 30 and 10% (using a 24-hour recall) in Egyptian women 12 . Levels of 29.7%, 16.2% and 17.6% during the first, second and third trimesters of pregnancy in Indonesia, a low-income country 31 , and underreporting of 5% for Cameroon 13 , have been reported. An earlier descriptive analysis of these data reported high underreporting in Jamaica, although levels were lower than in the United Kingdom 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This procedure defined so-called cut-off limits for EI/BMR, thereby providing limits below which EI must be recognized as being incompatible with long-term maintenance of energy balance and survival. This kind of procedure has been widely applied to indicate the quality of dietary reports, including those of pregnant women (16,30,37). However, for the following reasons this procedure is not appropriate for pregnant women: First, it assumes that subjects are in energy balance, an assumption that is rarely valid during pregnancy.…”
Section: Figurementioning
confidence: 99%